2001
DOI: 10.1002/1522-7278(2001)16:1<84::aid-tox100>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved carbon dioxide on the physiology and behavior of fish in artificial streams

Abstract: A new technology for treating waters contaminated with acid mine drainage involves the dissolution of limestone particles using carbon dioxide at pressures above ambient. Because of the fish health risks associated with episodes of high carbon dioxide levels in treated waters, we subjected three species of fish, brook trout (Salvelinus fontinalis), slimy sculpin (Cottus cognatus), and blacknose dace (Rhinichthys atratulus), to 24 h exposures of elevated dissolved carbon dioxide (CO2) at three levels, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Fish are commonly reported to “cough”, presumably as a result of the distinct CRG cough (Ballintijn, 1985; Ballintijn and Jüch, 1984; Ballintijn and Punt, 1985;; Burleson and Smith, 2001), and there is evidence that “cough” in fish can be modulated by acidity (Bishop and McIntosh, 1981; Hargis, 1976; Lunn et al ., 1976; Nevitt 1991; Rose-Janes and Playle, 2001; Ross et al . 2001; Satchell and Maddalena, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Fish are commonly reported to “cough”, presumably as a result of the distinct CRG cough (Ballintijn, 1985; Ballintijn and Jüch, 1984; Ballintijn and Punt, 1985;; Burleson and Smith, 2001), and there is evidence that “cough” in fish can be modulated by acidity (Bishop and McIntosh, 1981; Hargis, 1976; Lunn et al ., 1976; Nevitt 1991; Rose-Janes and Playle, 2001; Ross et al . 2001; Satchell and Maddalena, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Bishai [78] showed that juvenile brown trout (Salmo trutta) and Atlantic salmon (Salmo salar) demonstrated a stronger avoidance response to a pH change caused by CO 2 relative to a pH change caused by hydrochloric acid. Jones et al [79] noted that individual arctic char (Salvelinus aplinus) will avoid concentrations of CO 2 that exceed 50 µmol/L, Ross et al [80] showed that brook trout and blacknose dace (Rhinichthys atratulus) would avoid water with ≥2% CO 2 , while Clingerman et al [81] reported that intentional elevations of CO 2 to 60 mg/L in an aquaculture would induce avoidance behavior in groups of rainbow trout (Oncorhynchus mykiss), thereby facilitating harvest and collection in recirculating tanks. Finally, both Bernier and Randall [64], as well as Yoshikawa [82], revealed that rainbow trout exhibited a "violent" struggle upon being exposed to water maintained at 36-350 mmHg CO 2 , while Clingerman et al [81] indicated that rainbow trout in aquaculture tanks demonstrated "chaotic" swimming when CO 2 levels were increased to 35-60 mg/L.…”
Section: Co 2 and Fish Behaviormentioning
confidence: 99%
“…While the response of fishes to high concentrations of CO 2 when applied as an anesthetic appeared to be consistent [67,83], and the physiological responses of fishes to general hypercarbia had been well-defined [63], relatively less was known about the thresholds or "inflection points" that cause the onset of disturbances (i.e., a dose-response curve), and if those threshold concentrations were consistent across species and life stages. For example, Ross et al [80] exposed book trout, slimy sculpin (Cottus cognatus) and blacknose dace to four levels of CO 2 (0%, 1.4%, 2.8% and 5.1%) for either one or 24 h and noted differences in physiological responses both across species and across exposure durations, suggesting species-specific responses to CO 2 exposure. To address this need and define concentrations that induced onset of disturbances, Kates et al [66] exposed bluegill (Lepomis macrochirus), largemouth bass (Micropterus salmoides), silver carp (>450 mm) and bighead carp (>700 mm) to two different concentrations of CO 2 (30 mg/L and 70 mg/L) for three hours and showed that, 30 mg/L CO 2 (approximately 2000 µatm CO 2 ) had minimal physiological or behavioral impacts, but a three hour exposure to 70 mg/L CO 2 (approximately 50,000 µatm CO 2 ) resulted in a drop in ventilation rates, and an increase in irregular behaviors such as erratic swimming, twitching and escape attempts for silver carp and bighead carp [66].…”
Section: Co2 and Fish Behaviormentioning
confidence: 99%
“…The survey revealed that the data from these studies are of limited value to predict the fate of fishes in the future acidified oceans for the following reasons: (1) the pCO 2 levels used were much higher (above 50 000 µatm in 92% of the papers: 1 µatm = 0.76 × 10 -3 mmHg = 0.1013 Pa) than projected for the oceans in the next centuries (max. 1900 µatm at around the year 2300, Caldeira & Wickett 2003; see also Caldeira & Wickett 2005 for other projections), with only 2 studies covering the pCO 2 range below 2000 µatm (Jones et al 1985, Ross et al 2001; (2) CO 2 exposure periods were less than 4 d in 79% of the in vivo studies with only 8 experiments longer than 60 d; (3) marine species were used only in 25% of the studies; (4) research has focused largely on acid -base regulation and cardiorespiratory control (58% of the papers), and other aspects were little investigated; (5) effects on early development have been studied in only 2 papers (Kikkawa et al 2003, this paper was counted under 'sequestration, ' Sawada et al 2008);and (6) all are laboratory experiments.…”
Section: Introductionmentioning
confidence: 98%